Competitive pressure and corporate crime - Florian Baumann; Tim Friehe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This paper explores the relationship between the intensity of competition in product markets and firms' incentives to lower their production costs by illegal means. Our framework combines a Salop circle with a crime model à la Becker, allowing us to differentiate between several measures for the intensity of competition. We establish that more firms in the industry (i.e., lower entry costs) reduce the crime rate. Furthermore, whether more intense competition due to the increased substitutability of products raises or lowers the prevalence of criminal behavior can be clearly linked to the impact of such behavior on firms' production costs. Finally, we find that stricter law enforcement may entice more firms to enter the market, despite the higher expected sanction in the event of wrongdoing.
Keywords: K14; K23; L13; 330; product market competition; crime; deterrence; market entry